Evaluation of tear osmolarity measured by I-Pen osmolarity system in patients with dry eye - Park, Jongyeop; Choi, Youngjoo; Han, Gyule; Shin, Eunhae; Han, Jisang; Chung, Tae-Young; Lim, Dong Hui (Scientific reports, 2021)
This retrospective comparative study was to evaluate tear osmolarity measured by I-Pen osmolarity system (I-MED Pharma Inc, Dollard-des-Ormeaux, Quebec, Canada) in healthy subjects without dry eye disease (DED) and patients with DED, and its association with other ocular surface parameters. This study comprised 65 eyes of 65 patients. The ocular surface parameters including tear osmolarity with I-Pen osmometer of the patients who visited the refractive surgery center of Samsung Medical Center between January 1, 2020 and May 31, 2020 were retrospectively collected. The subjects were divided as asymptomatic normal group and symptomatic dry eye group. The distribution of tear osmolarity and its association with other ocular surface parameters were evaluated. Total thirty-two patients (32 eyes) were included in the control group, and 33 patients (33 eyes) were included in the DED group. Tear osmolarity was significantly higher in the DED group. Tear osmolarity was negatively correlated with tear break-up time, and the Schirmer test, and was positively correlated with Ocular Surface Disease Index symptom score. The cut-off value of 318 mOsm/L showed a sensitivity of 90.9% and specificity of 90.6% for diagnosing DED. The I-Pen osmometer can be considered suitable for use in the clinical setting, with good performance in DED diagnosis.